REGISTER PEMASOK UDANG DAN IKAN DI DESA KLUWUT KECAMATAN BULAKAMBA KABUPATEN BREBES - Fauzi, Muhammad Irfan (Sutasoma : Jurnal Sastra Jawa, 2017)
Register is one of the variations of the language background by social class, that is the range of occupational groups in every human society. One group of professions who use that language variation is a supplier of shrimp and fish in the Village District Kluwut Bulakamba Brebes or commonly called as the supplier. Their language is unique and different from the language used by society at large. The language also serves to hide their conversations from people outside the profession supplier. Therefore, the language register suppliers of shrimp and fish in the Village District Kluwut Bulakamba Brebes interesting to be studied and analyzed in terms of linguistic science. Problems in this research: 1) how to use the register form of shrimp and fish suppliers in the Village District Kluwut Bulakamba Brebes? and 2) whether the social function registers supplier of shrimp and fish in the Village District Kluwut Bulakamba Brebes? The purpose of this study was to describe the shape register used supplier of shrimp and fish in the Village District Kluwut Bulakamba Brebes and social function registers supplier of shrimp and fish in the Village District Kluwut Bulakamba Brebes. The research concluded that suppliers register shrimp and fish in the Village District Kluwut Bulakamba Brebes has two forms of registers, that is 1) the form of registers based on the formation process, and 2) the registers by unit lingual. Based on the formation process in the form of modifications with the addition of ji-at the beginning of words and syllables beheadings on the base and in the form of changes in the form of the reversal of the basic word order of the letters and the addition of the suffix-s even if not all of the vocabulary of an additional suffix-an. The form registers based unit lingual is singular, complex shapes (which had the affixation, reduplication, and composition), and form number. Social function registers supplier of shrimp and fish in the Village District Kluwut Bulakamba Brebes include functionality to ask the price, function shipping, transaction functions, chatting and joking function, the function asks contents by size (ses), and the function of asking the origin and species of shrimp. Based on this research, advice can be given are: 1) The use of registers to the general public is expected to be avoided, because the general public ignorance about the registers used by the supplier of shrimp and fish in the Village District Kluwut Bulakamba Brebes. 2) There are many more registers that can be used as an object of study for students who are interested in field of linguistics.